The relationship between e-learning service and student satisfaction a case study at the Syrian Virtual University (SVU) - Al Azmeh, Salma Ghassan (Business, Management and Economics Engineering, 2019)
Purpose – This study aims at exploring the impact of electronic services provided by the Syrian Virtual University (SVU) on student satisfaction. Besides, this study seeks to determine the dimensions of both electronic services and customer satisfaction at the SVU, and to what extent these dimensions may vary in accordance with different personal characteristics among students.Research methodology – A quantitative research method was adopted using an online questionnaire to collect data from students registering in different SVU programs.Findings – Overall, results were analysed using the SPSS: 18. The results indicated that the relationship between all electronic services dimensions and student satisfaction at the SVU were positively significant except for the bulk SMS dimension. Electronic service dimensions are also all applied throughout the SVU (SMS- Web Request- Facebook- email- Electronic library- Website- Learning Management System) respectively. Besides, results show that neither electronic services dimensions nor satisfaction dimensions vary with regards to gender, speciality and age. Furthermore, satisfaction dimensions such as privacy and security – ease of use – order fulfilment – customer service – electronic service portfolio are all applied in the SVU.Research limitations – The study in this paper is limited to only one university since the Syrian Virtual   University is the only virtual university in Syria. Also, the study focused only on university’s students, and not it is administrative staff.Practical Implications – the results of this paper are beneficial for the SVU future and other universities attempting to provide online services. Thus, results from advice the SVU to keep their services up-to-date with the latest technological improvements, especially the university’s website. This could be achieved by making it more users friendly and ultimately improve students’ satisfaction. Moreover, the SVU should highlight the bulk SMS service weaknesses and try to use it more efficiently. Furthermore, the SVU employees could use the results of this paper to segment their current and future services provided in the future correctly taking into account the differences between gender and other demographical factors.Originality/Value – This study is one of the first studies to investigate the relationships between E-Learning services and student satisfaction in virtual environments, especially the Syrian Virtual Universities SVU. Moreover, this study investigates specific dimensions regarding both E-services and student satisfaction and brings up a reliable model for further research.